1983
DOI: 10.1139/g83-068
|View full text |Cite
|
Sign up to set email alerts
|

Selection for light preference during ovipositing in Drosophila pseudoobscura

Abstract: Selection was carried out on a population of Drosophila pseudoobscura to obtain lines preferring high-light intensity or low-light intensity during oviposition. This species is generally characterized as preferring low-light intensities. It was possible to select for increased preference for high-light intensity, but not for low-light intensity during oviposition. However, additive genetic variability exists in preferences for both high- and low-light intensities. The original population was probably operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…When given a choice between different light intensities, females exhibited a strong preference for brighter light. These results indicated that G. molesta females were sensitive to light intensity and, as such, they may be able to sense differences in the distribution of light intensities between host plant leaves in sunny and shaded sites, and to use light cues to accurately oviposit on sunny sites in natural conditions, just as diurnal species do (Seiger & Sanner, 1983; Wogaman & Seiger, 1983; Yang, 2006). Connor (2006) showed opposite responses to light in the leaf‐mining moth Cameraria hamadryadella (Clemens), and suggested that ovipositing females do not discriminate between sunny or shaded leaves.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…When given a choice between different light intensities, females exhibited a strong preference for brighter light. These results indicated that G. molesta females were sensitive to light intensity and, as such, they may be able to sense differences in the distribution of light intensities between host plant leaves in sunny and shaded sites, and to use light cues to accurately oviposit on sunny sites in natural conditions, just as diurnal species do (Seiger & Sanner, 1983; Wogaman & Seiger, 1983; Yang, 2006). Connor (2006) showed opposite responses to light in the leaf‐mining moth Cameraria hamadryadella (Clemens), and suggested that ovipositing females do not discriminate between sunny or shaded leaves.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Yang (2006) has reported that the oviposition density of the periodical cicada, Magicicada spp., is affected by the ambient light of host plants in the field, with most eggs laid on plant areas with high light exposure. Given a choice between light intensities, Drosophila persimilis Dobzhansky and Epling prefer to lay eggs in high light intensity, whereas Drosophila pseudoobscura Frolova exhibit a preference for low light intensity (Richardson & Johnston, 1975; Seiger & Sanner, 1983; Wogaman & Seiger, 1983). However, oviposition responses to light are primarily found in insects that lay eggs during the day.…”
Section: Introductionmentioning
confidence: 99%
“…In general, behaviour of an organism is strongly influenced by environmental conditions Effect of different external factors on oviposition pattern has been investigated in various Drosophila species (Gruwez et al, 1971;Mckenzie, 1975;Ohnishi, 1977;Rockwell & Grossfield, 1978;Seiger & Sanner, 1983;Schnebel & Grossfield, 1986). Temperature plays an important role in oviposition behaviour of Drosophila species.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, Wogaman and Seiger (1983) were able to distinguish between populations of Drosophila on the basis of their light preference during oviposition. Further, selection experiments showed that these light preferences are under genetic control (Seiger and Sanner, 1983). In addition, sympatric species could be distinguished on the basis of their choice of an oviposition site.…”
mentioning
confidence: 99%